2016
DOI: 10.1063/1.4941053
|View full text |Cite
|
Sign up to set email alerts
|

Non-adiabatic dynamics of molecules in optical cavities

Abstract: Strong coupling of molecules to the vacuum field of micro cavities can modify the potential energy surfaces thereby opening new photophysical and photochemical reaction pathways. While the influence of laser fields is usually described in terms of classical field, coupling to the vacuum state of a cavity has to be described in terms of dressed photon-matter states (polaritons) which require quantized fields. We present a derivation of the non-adiabatic couplings for single molecules in the strong coupling regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
234
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(238 citation statements)
references
References 30 publications
4
234
0
Order By: Relevance
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In such theoretical descriptions, the molecules are usually treated with a reduced number of degrees of freedom or with some simplified models assuming two-level systems [20]. However, it is worth studying single-molecule cavity interactions as well, since a more detailed study of individual objects may also provide meaningful results [22,23,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The n-body cascading terms similarly behave like vertex insertions with 2n free branches. An interesting future extension of this work would be to consider manipulating the cascading signal from a system of molecules embedded in an optical cavity, systems which have drawn recent interest [39][40][41][42][43][44]. Optical cavities alter the density of electromagnetic field modes from its free-space value, suppressing cascading in all but the cavity mode.…”
Section: Discussionmentioning
confidence: 99%
“…Polaritonic chemistry, i.e., the potential to manipulate chemical structure and reactions through the formation of polaritons (hybrid light-matter states) was experimentally demonstrated in 2012 [7], and has become a topic of intense experimental and theoretical research in the past few years [8][9][10][11][12][13][14][15][16][17][18]. However, existing applications and proposals have been limited to enhancing or suppressing the rates of single-molecule reactions.…”
mentioning
confidence: 99%
“…This means that the quantum yield ϕ ¼ N prod =N phot of the reaction, which describes the percentage of molecules that end up in the desired reaction product per absorbed photon, has a maximum value of 1. This limit can be overcome in some specific cases, such as in photochemically induced chain reactions [2-4], or in systems that support singlet fission to create multiple triplet excitons (and thus electron-hole pairs) in solar cells [5,6].Polaritonic chemistry, i.e., the potential to manipulate chemical structure and reactions through the formation of polaritons (hybrid light-matter states) was experimentally demonstrated in 2012 [7], and has become a topic of intense experimental and theoretical research in the past few years [8][9][10][11][12][13][14][15][16][17][18]. However, existing applications and proposals have been limited to enhancing or suppressing the rates of single-molecule reactions.…”
mentioning
confidence: 99%